2000
DOI: 10.1111/j.1365-2133.2000.03703.x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of skin cancer in 5356 patients following organ transplantation

Abstract: We conclude that organ transplant recipients are at a highly increased risk for non-melanoma skin cancer and must be closely followed throughout their lives. Cancer risk associated with transplantation is higher for sun-exposed than for non-sun-exposed epithelial tissues, even among populations living in regions with low solar insolation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
124
0
3

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 237 publications
(130 citation statements)
references
References 46 publications
3
124
0
3
Order By: Relevance
“…Although cancer risk following organ transplantation has been analysed in several prospective studies, only few of them were population based with long-term follow-up (Hoover and Fraumeni, 1973;Kinlen et al, 1979;Birkeland et al, 1995Birkeland et al, , 2000Hoshida et al, 1997;Kyllonen et al, 2000;Lindelof et al, 2000), and except for one of the studies (Lindelof et al, 2000), none of them included patients with another transplanted organ than a kidney. While components of our study have been included in earlier analyses (Birkeland et al, 1995) and chiefly in a publication focused on skin cancer (Lindelof et al, 2000), the cohort has now been expanded and the follow-up time added.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although cancer risk following organ transplantation has been analysed in several prospective studies, only few of them were population based with long-term follow-up (Hoover and Fraumeni, 1973;Kinlen et al, 1979;Birkeland et al, 1995Birkeland et al, , 2000Hoshida et al, 1997;Kyllonen et al, 2000;Lindelof et al, 2000), and except for one of the studies (Lindelof et al, 2000), none of them included patients with another transplanted organ than a kidney. While components of our study have been included in earlier analyses (Birkeland et al, 1995) and chiefly in a publication focused on skin cancer (Lindelof et al, 2000), the cohort has now been expanded and the follow-up time added.…”
Section: Discussionmentioning
confidence: 99%
“…Two of four centres (Stockholm and Gothenburg) were not covered by the in-patient registry until 1972 and onwards. Some 50 organ transplantations performed at these centres during 1970 and 1971 were therefore not included in our study cohort (Lindelof et al, 2000) unless they were retransplanted after 1971; if so, the date of retransplantation would be erroneously recorded as the first transplantation. The surgical codes used for selection were the following: 6070 (kidney), 5530, 5531 (pancreas), 5200, 5202 (liver), 3590 (lung) and 3085 (heart).…”
Section: Definition Of Study Cohortmentioning
confidence: 99%
“…Of note, among OTRs, the risk of skin cancer has been correlated with cumulative UV radiation exposure 21 ; however, many studies in northern European countries with less intense UV exposure have shown no significantly increased risk of melanoma in OTRs. [22][23][24] MELANOMA IN SOLID ORGAN TRANSPLANT RECIPIENTS Solid organ transplant recipients are a well-studied group of immunocompromised patients. Among these individuals, an increased incidence of both nonmelanoma skin cancer and melanoma has been reported extensively.…”
Section: Article Highlightsmentioning
confidence: 99%
“…Of note, in the studies in which risk was reported on the basis of sex, men generally had an increased risk of melanoma compared with women. 23,24,38 All things considered, although the majority of these large population-based studies of OTRs have shown an increased risk of melanoma, the relative risk is still much lower than that of nonmelanoma skin cancers. 40,41 By comparison, the incidence of nonmelanoma skin cancers posttransplant is increased 50-to 250-fold for squamous cell carcinoma and 10-fold for basal cell carcinoma.…”
Section: Article Highlightsmentioning
confidence: 99%
See 1 more Smart Citation